Research on the evolutionary game and simulation of multiple subjects’ behavior in the reconstruction of old urban residential communities - Yongchang Jiang; Yanjun Dong (PLoS ONE, 2026)
The successful execution of the reconstruction of old urban residential communities, a significant project that affects people’s livelihoods, depends on the cooperative efforts of several subjects. However, existing research predominantly focuses on dyadic interactions between governments and residents, neglecting the critical role of third-party enterprises. This study advances the field by developing a tripartite evolutionary game model encompassing the governments, district residents, and third-party enterprises, which we simulate using Matlab and empirically examined based on the case studies. The study’s findings demonstrate that, regardless of the strategies selected by the various participants, the final strategy selections will converge to the stable equilibrium state of (1,1,1). In addition, the primary factors influencing each participant’s strategy selections are the governments incentive mechanism, the cost of renovation for district residents, and the profits and losses of third-party enterprises. These insights provide both theoretical advancements in multi-stakeholder urban governance models and practical guidance for optimizing collaborative dynamics, mitigating social tensions, and improving the overall efficacy of community renewal initiatives.